Relationship between health belief model constructs and elementary teachers use of food rewards - Daniels, Elizabeth (Kansas State University, 2024)
Background: Teachers’ actions can influence student health and eating preferences. However, few school policies adequately address classroom food practices. Despite recommendations to the contrary, food rewards are often used to manage student behavior or to recognize academic success. Objective: To examine the association between elementary teacher use of food rewards and constructs of the Health Belief Model (HBM). Methods: Elementary school teachers (n = 256) from schools located within the midwestern region of the United States completed an online survey which included demographic questions and rating scales to measure a) the types and frequency of classroom food rewards, b) perceived health and wellbeing threats associated with the use of food rewards, c) perceived barriers to refraining from the use of food rewards, and d) awareness of food policy cues relating to classroom food rewards. Pearson correlation coefficients were used to measure the association between food reward frequency and scores for each of the HBM constructs. Multiple regression analysis was used to predict food reward frequency and scores for perceived threat, perceived barriers to refraining from the use of food rewards, and school food policy cues. Results: With 56% of teachers reporting its use at least occasionally, candy was the most frequently utilized food reward. Additionally, all but 14% (n = 35) reported that they used food rewards during the 30-day period prior to the survey. A majority of teachers either disagreed or strongly disagreed that using food rewards would lead to poor eating habits (n = 156, 61.3%) or would distort a child’s relationship with food (n = 142, 55.5%). In the bivariant analysis, food reward frequency was negatively correlated with school food policy cues (r = -.22, p < .01) and positively correlated with barriers to refraining from using food rewards (r = .47, p < .01). The multiple regression analysis predicted food reward frequency [R² = 22, F (3,247) 23.62, p < .001], but only barriers refraining from using food rewards (β = .45; p < .001) contributed significantly to the prediction. Conclusion: Teachers do not understand the risks associated with the use of food rewards. Barriers to refrain from using food rewards, but not perceived threat or school food policy cues to action, influenced the frequency of food rewards in this sample of elementary school classrooms. The findings of this study have future implications for efficacious policy and training for the discontinuation of the use of food rewards in classrooms
Keywords: Child nutrition; School nutrition; Food rewards; Wellness policy